Enabling narrative through design. (8th May 2021) - Jordan, Patrick W.; Bardill, Andy; Herd, Kate; Grimaldi, Silvia
Psychological wellbeing is profoundly influenced by our self-narratives, and products and services can play a role in affecting these. We looked at desired self-narratives within a tightly-defined user group - Young Creatives . We evaluated Jung's 12 archetypes as a means of classifying these narratives. We also investigated the ways in which narratives are enabled through products and services. Participants (N = 56) described two scenarios where they had expected a particular narrative would be enabled - one where it was and one where it was not. They also described the ways in which they expected it to be enabled. Analyses suggested that the Jung's classification gave useful, meaningful and valid insights into our user group. They also indicated that users expected different narratives to be enabled in different ways. Some narratives were more likely to be enabled than others, depending on the extent to which affecting them was within the user's control.